Aggregate index of systemic inflammation as a novel prognostic biomarker in Chinese patients with acute decompensated heart failure: a population-based real-world study - Hu, Lin; Deng, Yangjie; Liu, Chuanjin; Kuang, Yinghao; Huang, Xinfang; Zhang, Jinyan; Huang, Wanfen; Jian, Yafei; Xie, Guobo; Zou, Yang; Zhang, Shuhua (Frontiers in Endocrinology, 2025)
IntroductionInflammation is hypothesized as an early trigger for decompensation in heart failure patients. This study aims to evaluate the prognostic value of a novel inflammatory biomarker, the Aggregate Index of Systemic Inflammation (AISI), for predicting 30-day mortality in patients with acute decompensated heart failure (ADHF).MethodsThis analysis included 2,765 patients from the Jiangxi-ADHF II registry (2018-2024). Complete blood counts were measured at hospital admission, with 30-day mortality outcomes followed. Multivariable Cox proportional hazards model was employed to analyze the association between AISI and all-cause mortality.ResultsDuring 30-day follow-up, the overall mortality rate was 7.34% (203 deaths), with rates progressively increasing across AISI quartiles (Q1-Q4: 2.32%, 3.33%, 5.21%, 18.50%). Compared with the lowest AISI quartile, the highest quartile was associated with a 210% higher risk of 30-day mortality (Hazard Ratio: 3.10, 1.62-5.94). This association remained robust across multiple sensitivity analyses, including subgroup analysis, temporal sensitivity assessments, and data integrity verification. Further spline regression analysis revealed a U-shaped curve association between AISI (and LnAISI) and 30-day mortality in ADHF patients (P for non-linearity < 0.05). In general, both extremely low and high levels of AISI and its natural logarithm (LnAISI) were associated with an increased risk of 30-day mortality in ADHF patients. Moreover, in predicting 30-day mortality among ADHF patients, the AISI demonstrated significantly superior predictive value compared to white blood cell count, neutrophil count, monocyte count, and lymphocyte count (Area under the curve=0.77; all DeLong tests P <0.05), with an optimal threshold of 925.44.DiscussionThis population-based retrospective cohort study demonstrated the predictive value of AISI for short-term outcomes in Chinese ADHF patients. Compared to conventional inflammatory biomarkers, AISI significantly improved the predictive performance for 30-day mortality in ADHF patients. These findings may facilitate optimized prevention of adverse outcomes in ADHF and enable early risk stratification through targeted assessment of individual ADHF patients.